2013
DOI: 10.3389/fendo.2013.00134
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Specific Cytokine Assays in Tissue Samples from a Bottlenose Dolphin with Hyperinsulinemia

Abstract: Chronic inflammation has been associated with insulin resistance and type 2 diabetes (T2D) in humans. Postmortem hepatic and splenic tissue from a 46-year-old geriatric male bottlenose dolphin (Tursiops truncatus) with insulin resistance (chronic hyperinsulinemia with hyperglycemia), chronic inflammation (white blood cell count greater than 12,000 cells/μL), and mild fatty liver disease was evaluated for elevated pro-inflammatory mediators. Cytokine mRNA expression in postmortem hepatic and splenic tissue, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Cytokines are important mediators of the immune response, and several studies have explored the use of cytokines to relate to health status of marine mammals in different manners. Amplification of mRNA for cytokines using quantitative reverse-transcription polymerase chain reaction (qRT-PCR) to quantify cytokine expression in marine mammals, with or without stimulation of PBMCs, has been used in several studies (18, 4653). While useful to measure responsiveness to a signal, the quantification of mRNA does not necessarily represent the circulating bioactive protein, which requires important steps, in which translation and secretion need to take place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines are important mediators of the immune response, and several studies have explored the use of cytokines to relate to health status of marine mammals in different manners. Amplification of mRNA for cytokines using quantitative reverse-transcription polymerase chain reaction (qRT-PCR) to quantify cytokine expression in marine mammals, with or without stimulation of PBMCs, has been used in several studies (18, 4653). While useful to measure responsiveness to a signal, the quantification of mRNA does not necessarily represent the circulating bioactive protein, which requires important steps, in which translation and secretion need to take place.…”
Section: Discussionmentioning
confidence: 99%
“…While powerful at associating cytokine production with specific cell types using simultaneous extra-cellular labeling, this approach is tedious and time consuming, and allows the labeling for a relatively low number of cytokines at a time, in this case only two cytokines. Similarly, immunohistochemistry has been used to detect cytokines in cetacean tissue section (53, 55, 56). While informative on the distribution of the cell types secreting cytokines in different tissues, this method is limited to the use of tissues from dead animals, or biopsies in live animals, which would be a rather invasive procedure.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have used cross-reactive antibodies specific for human, mouse, porcine, and bovine on cetacean samples [ 5 , 13 , 14 ]. However, cross-species reactivity of available Ab to cytokines or chemokines cannot be universally expected for all cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Increased production of a variety of pro-inflammatory cytokines is the hallmark for many diseases. Using real-time qPCR and fluorescent IHC, Eberle et al showed that a dolphin with hyperinsulinemia, hyperglycemia, chronic inflammation, and fatty liver disease displayed a similar pro-inflammatory state as humans with type 2 diabetes and hyperinsulinemia [ 5 ]. Tumor necrosis factor-alpha (TNF-α) and interferon-gamma (IFN-γ) are two cytokines specifically useful to measure the inflammatory state of an animal [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Neeley et al’s discovery of disrupted associations between adiponectin and glucagon in dolphins with high insulin and iron overload, paired with high sequence similarity of dolphin and human adiponectin, continue to support increasing high-weight adiponectin as a potential therapeutic target for people and other animals with these diseases ( 16 ). Dr. Kirsten Eberle et al use their newly developed, dolphin-specific immunoassays to characterize inflammation present in a 46-year old dolphin with metabolic syndrome and iron overload compared to a dolphin without these diseases ( 17 ). Parallels in chronic inflammation among people and dolphins with metabolic syndrome are reported, enhancing the emerging story of chronic inflammation and metabolic perturbations.…”
mentioning
confidence: 99%